2012
DOI: 10.1038/cddis.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoacridinone-dependent lysosomal photodestruction: a pharmacological Trojan horse approach to eradicate multidrug-resistant cancers

Abstract: Multidrug resistance (MDR) remains a primary hindrance to curative cancer therapy. Thus, introduction of novel strategies to overcome MDR is of paramount therapeutic significance. Sequestration of chemotherapeutics in lysosomes is an established mechanism of drug resistance. Here, we show that MDR cells display a marked increase in lysosome number. We further demonstrate that imidazoacridinones (IAs), which are cytotoxic fluorochromes, undergo a dramatic compartmentalization in lysosomes because of their hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…The results obtained point out that accumulation of C1330 in particular structures is crucial for the effective photokilling of C. albicans cells. In accordance with observations made by others (3,26,29), we observed that the nucleus is not the only structure where C1330 accumulates (30 min at 100 M) (Fig. 6A).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results obtained point out that accumulation of C1330 in particular structures is crucial for the effective photokilling of C. albicans cells. In accordance with observations made by others (3,26,29), we observed that the nucleus is not the only structure where C1330 accumulates (30 min at 100 M) (Fig. 6A).…”
Section: Discussionsupporting
confidence: 93%
“…Imidazoacridinones accumulate effectively in lysosomes of tumor cells, due to their weak base nature. Alkalization of the cells with bafilomycin or ammonium chloride abolished selective accumulation of IA in cell lysosomes and promoted accumulation in the nucleus (26). Under our experimental conditions, we observed that in C. albicans cells, C1330 accumulated efficiently in the nucleus.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Vesicles that reside intracellularly have also been implicated in resistance to antiangiogenic therapy. This relates to the sequestration and accumulation of therapeutic compounds in the lysosomes and endocytic vesicles, a phenomenon that has already been described for chemotherapeutics Adar et al, 2012) and photosensitizing compounds . We recently showed that this also applies to one of the antiangiogenic TKIs, i.e., sunitinib.…”
Section: F Emerging Mechanisms Of Resistancementioning
confidence: 97%